Penerapan Komunikasi bahasa jawa pada Anak Usia Dini - Siti Ratnawati (Departement of Mathematics Education, 2024)
Language has various forms and characteristics for use in daily communication in each region. One of them is the Javanese language used in Central Java. However, the implementation of the Javanese language in early childhood is almost extinct due to the lack of daily communication practices in their environment, both at home and in school. Nowadays, millennial parents rarely communicate with their children using their mother tongue (Javanese). Parents are more accustomed to communicating with their children using the Indonesian language. As a result, communication between parents and children no longer uses the Javanese language. Therefore, a more in-depth study is needed in this regard. This study aims to implement the Javanese language, especially the krama language, as the object of observation. The data collection techniques used are observation and interviews. The results show that the Javanese language, especially the krama language, can be applied to early childhood through daily habits practiced by children and their environment in interacting.